Cinnamaldehyde and its combination with deferoxamine ameliorate inflammation, ferroptosis and hematoma expansion after intracerebral hemorrhage in mice - Liu, Yulin; Yang, Guoqiang; Liu, Mengnan; Zhang, Yuwei; Xu, Houping; Mazhar, Maryam (Journal of neuroinflammation, 2025)
Intracerebral hemorrhage (ICH) is a most serious type of hemorrhagic stroke with a continuously rising incidence globally, without effective cure available. The underlying mechanisms driving brain injury are complex and include inflammation, oxidative stress, glutamate excitotoxicity, membrane damage, lipid peroxidation, ferroptosis and other cellular death modes. Hematoma clearance is the key to limit brain damage and foster the recovery process. The quest for effective ICH remedies is continuing and strategically evolving with the expansion of knowledge and understanding of target mechanisms and novel lead compounds. In this study, we have investigated the effects of cinnamaldehyde after ICH as an individual treatment as well as in combination with deferoxamine. The autologous blood injection model was employed using C57BL/6 mice. Following 2 h of ICH induction, animals received IP injection once per day for three days; normal saline in ICH model group, cinnamaldehyde, deferoxamine, and combined cinnamaldehyde and deferoxamine in respective groups. Measurement of neurobehavioral scoring, markers of inflammation NFкB, TNFα, IL-1, IL6, iNOS; oxidative stress and ferroptosis GSH, TBARS, glutamate, choline containing phospholipids, GPX4, SLC7A11, SLC40A1, ACSL4; and hematoma clearance hemoglobin, haptoglobin, hemopexin, zonulin, CD163, LRP1, HO1, CD36, CD206, were investigated using ELISA, PCR, and western blot. Immunofluorescence for NeuN/SLC40A1, GFAP/GPX4, NeuN/HO1, Iba1/HO1 was also performed. We have found that cinnamaldehyde possess anti-inflammatory, antioxidant, anti-ferroptotic and hematoma limiting properties that were comparable to those obtained with deferoxamine. However, combination of cinnamaldehyde and deferoxamine demonstrated remarkable effectiveness in restoration of these parameters indicating their synergistic effect in ICH model.